Binômio: necrofilia e biofilia nas teorias pedagógica, psicológica e psicanalítica (Freire, Fromm e Freud) - Abreu, Joel Santos de (2021)
This thesis had as its object of study the binomial: necrophilia (in the connotative sense, in figurative language) and biophilia from the perspective of Paulo Freire's pedagogical and humanist thinking and the psychologist Erich Fromm, expanded, deepened and enriched with mentions from other categories of Sigmund Freud's Psychoanalysis. Due to the influence of Fromian ideas, the Brazilian educator also used these same terms, with opposite meanings among themselves, to support many of his speeches, which are, mainly, the content of his masterpiece: Pedagogy of the oppressed, for relating to the challenge of establishing an educational process of liberating philosophy and social transformation. This is because, for a long time, a perverse and sophisticated system of policies and cultures of control and dehumanization of the mass considered inferior has been implanted in society, by the economically favored, hegemonic and oppressive class. The unscrupulous purpose is to hinder the natural propensity of each subject to be more, to make him a “thing”, an object, and, thus, to behave similarly to irrational servant animals fully submissive in complying with their owners' orders and whims. Worse still, being totally liable to be similar to a corpse subjected to a necrophilic relationship so that the pleasures of these people with psychic disorders are carried out, regardless of consent, whose obsession is to subject everything that may fulfill their desires. The history of Brazil, since its colonization, presents vast reports of Europeans subjugating the natives and enslaving other races. The emergence of the logic of Darwinian theory corroborated his prejudices. The problems arising from domination and oppression are motivated by the sadistic selfishness of a group of wealthy and insatiable greed, whose pretensions are to increase, more and more, their powers with appropriations of everything and control of all, covering the dimensions of existence, such as politics, economics, education, culture, religion etc. Opposed to this cruel system imposed by the minority of high and powerful acquisitive condition, there are the majority of human beings, who love life; aspires for solidarity, fraternal coexistence; aims for a better world, governed by the principles of justice and democracy.